640. ESOPHAGECTOMY FOR ESOPHAGEAL AND GASTROESOPHAGEAL JUNCTION ADENOCARCINOMA IN RYGB PATIENTS. A LITERATURE REVIEW ON OPERATIVE TECHNIQUES, SAFETY AND ONCOLOGIC OUTCOME. (24th September 2022) - Diab, Abdul-Rahman; DuCoin, Christopher
Abstract: Roux-en-Y gastric bypass (RYGB) surgery changes the anatomy of the gastrointestinal tract, and thus renders the surgical management of esophageal and gastroesophageal junction adenocarcinoma cases technically confusing. No consensus exists regarding the the optimal surgical technique in terms of safety and oncologic outcomes in these cases. The aim of this study is to compile and analyze the available operative/technical data in the literature on surgical management of esophageal and gastroesophageal junction adenocarcinoma in RYGB patients. A literature review was performed in Cochrane Database, Embase, Medline, PubMed, and Scopus electronic databases to find all cases of esophagectomy for esophageal and gastroesophageal junction adenocarcinoma in RYGB patients. Keywords used were esophageal adenocarcinoma, esophagogastric junction adenocarcinoma, gastric bypass, bariatric surgery, esophagectomy, Ivor Lewis esophagectomy, transhiatal esophagectomy, and thoracoabdominal esophagectomy. All abstracts retrieved were screened, and for each one deemed relevant, the full text was obtained. Finally, 11 articles containing 17 cases were studied and analyzed. Extracted data included: Esophagectomy type, incision type, gastric pouch management, conduit used, Roux limb management, and most importantly complications and oncologic outcome. Esophagectomy was Ivor Lewis, transhiatal, and thoracoabdominal in 58.82%, 23.53% and 17.65% respectively. Esophagectomy was open in 46.67%, and minimally invasive in 53.33%. Gastric pouch was reconnected to the excluded stomach in 14.29%, while it was resected in 85.71%. Gastric, colonic and jejunal conduits were used in 87.5%, 6.25% and 6.25% respectively. In 63.64%, the Roux limb (RL) was connected to the abdominal wall and a feeding jejunostomy was placed. In the remaining 36.36%, the RL was either totally resected, or its proximal end was anastomosed to the distal end of the biliopancreatic limb. No complications were reported. No differences in oncologic outcome or safety were observed between open versus minimally invasive esophagectomy. Minimally invasive esophagectomy is safe and technically feasible with appropriate oncologic outcomes for esophageal and gastroesophageal junction adenocarcinoma patients with previous gastric bypass. Therefore open esophagectomy is not necessary. Post RYGB Esophageal and gastroesophageal junction adenocarcinoma might be underreported, and the number of cases will undoubtedly continue to increase in the coming years.